2014
DOI: 10.1111/1365-2435.12268
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance landscapes in thermal ecology

Abstract: Summary1. How thermal tolerance estimated in the laboratory can be extrapolated to natural settings remains a contentious subject. Here, we argue that the general premise that a single temperature can accurately describe upper or lower tolerance limits is incorrect. 2. Survival probability is determined by both the intensity and the duration of a thermal stress, and the association between these variables can be adequately conveyed by a thermal tolerance landscape. Employing this framework, we demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
484
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 320 publications
(515 citation statements)
references
References 53 publications
(143 reference statements)
26
484
4
1
Order By: Relevance
“…Feder, 1978Feder, , 1982Tsuji, 1988;Stillman and Somero, 2000;Stillman, 2002Stillman, , 2003Rezende et al, 2014). Its CTMax of nearly 41 • C is the highest reported here, however this is the same temperature recorded in tide pools during heat waves, in southeastern Brazil (Supplementary material), where specimens were captured.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Feder, 1978Feder, , 1982Tsuji, 1988;Stillman and Somero, 2000;Stillman, 2002Stillman, , 2003Rezende et al, 2014). Its CTMax of nearly 41 • C is the highest reported here, however this is the same temperature recorded in tide pools during heat waves, in southeastern Brazil (Supplementary material), where specimens were captured.…”
Section: Discussionsupporting
confidence: 67%
“…Stillman (2003) explored the interspecific variability in response to warming in porcelain crabs (genus Petrolisthes) and found that species with the greatest tolerance to high temperatures displayed the smallest acclimation capacity. Additionally, Rezende et al (2014) demonstrated that the temperature range that an organism can tolerate is expected to narrow down with the duration of the thermal challenge, suggesting that a trade-off exists between tolerance to acute and chronic exposition to thermal stress. These findings suggests that species with the higher thermal limits may be the most vulnerable to small sustained increases in temperature, this way, tropical species appear as the most vulnerable to global warming (Somero, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The results from the present study agree with this conclusion, since organisms with different body shapes and surface/volume ratios, such as crabs and shrimp/fish were tested, and crab's response was different from that of shrimp/fish. Additionally, Rezende et al (2014) demonstrated that the temperature range that an organism can tolerate is expected to narrow down with the duration of the thermal challenge, suggesting that a trade-off exists between tolerance to acute and chronic exposition to thermal stress. These authors suggest that the use of thermal tolerance landscapes, which include both the time of exposure and temperature, will be more adequate in providing an index of thermal tolerance that is ecologically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Predictions are based on the thermal performance curves in Fig. 1 Kingsolver et al, 2004;Rezende et al, 2011Rezende et al, , 2014. More generally, optimal and maximal temperatures are frequently greater for shortterm (e.g.…”
Section: Time Scale and Thermal Performance Curvesmentioning
confidence: 99%
“…However, many studies have shown that the duration of exposure can influence performance even for non-lethal temperatures, and the thermal range for performance can decrease with increasing duration of exposure (Rezende et al, 2014). For example, for larval growth in insects, body temperatures that maximize growth rates at short time scales (4-24 h) can be suboptimal or even lethal over longer time scales (Reynolds and Nottingham, 1985;Kingsolver and Woods, 1997;Kingsolver, 2000;Petersen et al, 2000;Kingsolver et al, 2004;Kingsolver and Nagle, 2007).…”
Section: Introductionmentioning
confidence: 99%